2023
DOI: 10.1155/2023/5560605
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modeling and Evaluation of Potential mRNA and Peptide‐Based Vaccine against Marburg Virus (MARV) to Provide Immune Protection against Hemorrhagic Fever

Abstract: A hemorrhagic fever caused by the Marburg virus (MARV) belongs to the Filoviridae family and has been classified as a risk group 4 pathogen. To this day, there are no approved effective vaccinations or medications available to prevent or treat MARV infections. Reverse vaccinology-based approach was formulated to prioritize B and T cell epitopes utilizing a numerous immunoinformatics tools. Potential epitopes were systematically screened based on various parameters needed for an ideal vaccine such as allergenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Several reverse vaccinology or immunoinformatic (in silico only) studies of Marburg structural proteins have been recently published [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. The bulk of these studies limited their characterization of potential T cell epitopes to the envelope glycoproteins, VP 24 matrix protein, VP30 transcription factor, VP35 polymerase cofactor, and VP matrix protein of MARV [ 46 , 51 , 56 , 57 ]. However, two studies reported on potential HLA class I or class II-restricted T cell epitopes within the MARV nucleoprotein [ 49 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reverse vaccinology or immunoinformatic (in silico only) studies of Marburg structural proteins have been recently published [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. The bulk of these studies limited their characterization of potential T cell epitopes to the envelope glycoproteins, VP 24 matrix protein, VP30 transcription factor, VP35 polymerase cofactor, and VP matrix protein of MARV [ 46 , 51 , 56 , 57 ]. However, two studies reported on potential HLA class I or class II-restricted T cell epitopes within the MARV nucleoprotein [ 49 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the Marburg proteome was screened to identify potential immunogenic epitopes that bind to human MHC molecules. However, previous reports have focused solely on bioinformatics and in silico screening studies [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ] for human MHC molecules. Our contribution involves a bioinformatics analysis of potential immunogenic T cell epitopes specific to human MHC class I (i.e., HLA–A and B) and Cynomolgus MHC class I (Mafa MHC–A).…”
Section: Introductionmentioning
confidence: 99%